HUBUNGAN PENGETAHUAN IBU DAN INISIASI MENYUSUI DINI DENGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF PADA BADUTA: The relationship of mother's knowledge and early initiation of breastfeeding with a historyof exclusive breastfeeding history in under fives - Khasanah, Tri Ardianti; Allifiya, Bella Nur (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2023)
According to the Riskesdas 2014 – 2018, coverage of exclusive breastfeeding in Indonesia in 2014 amounted to 37.3%, 2015 amounted to 55.7%, 2016 amounted to 54%, 2017 amounted to 61.33%, and in 2018 experienced a significant decrease, namely by 37.3%. According to SSGI (2021), only 52.5% or half of the 2.3 million babies aged less than six months are exclusively breastfed. This research was conducted in the Central Bogor Health Center UPTD area from June to May 2023 with a cross-sectional design using a purposive sampling technique involving 67 respondents. Data collection included filling out mother's knowledge questionnaires, early initiation of breastfeeding, and history of exclusive breastfeeding. The statistical analysis used was the chi-square test. The results of the study showed that 61.2% of respondents who had babies aged 6-24 months with the exclusive breastfeeding category and 38.8% were not exclusively breastfed. The results of the bivariate test study found that there was a significant relationship between knowledge and exclusive breastfeeding (p-value 0.000) and there was no significant relationship between Early Breastfeeding Initiation and a history of exclusive breastfeeding (p-value 0.932).